Learning to Reflect in Online Fantasy Role-Playing Games - Medeni, Tunç D.; Miyata, Kazunori; Sağsan, Mustafa (Information World, 2009)
The online role-playing games and their virtual communities, which are free and run by volunteers, attract much attention from business and academics, although studies on smaller gaming communities are still limited. One of these small online fantasy roleplaying communities, the world of Wold, is researched, using participant observation and Internet interviewing techniques within an e-research framework. After providing background information about the research, the paper then presents the conceptual framework, which consists of three main parts: (1) use of asynchronous communication tools for learning and reflection, (2) conceptualization of reflection, and (3) role of roleplaying and storytelling in reflection and learning. In the light of this framework, research findings about the learning and reflection that occurs at (1) intrapersonal, (2) personal and (3) interpersonal levels in online role-playing games will be discussed. The paper will then be concluded by research implications and limitations. It is hoped that, relating to learning in terms of developing sustainable virtual communities for reflective learning, this research will provide insights into the function of multiplayer games for serious purposes like learning and socialization, as well as the role of hard technology for soft purposes like reflective learning and practice.